Association of neutrophil-to-lymphocyte ratio and microalbuminuria in patients with normal eGFR - Kutlugun Aysun Aybal; Ebinc Fatma Ayerden; Ozturk Mujgan Tek; Efe Fatma Kaplan; Karadag İbrahim; Eser Murat; Unsal Oktay; Karakaya Serdar (Sciendo, 2018)
Aims. The aim of this study was to evaluate the association between neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and microalbuminuria in patients with normal estimated glomerular filtration rate (eGFR).